2020
DOI: 10.1097/pec.0000000000002064
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' Approach to Anaphylaxis in Childhood

Abstract: Objectives: Anaphylaxis is a life-threatening, severe, generalized, or systemic hypersensitivity reaction. The incidence of anaphylaxis is increasing especially in pediatric age. Our aim in this study was to investigate the knowledge and attitudes of the physicians on the diagnosis and treatment of anaphylaxis.Methods: A questionnaire form consisting of a total of 18 questions was prepared. Six questions concerned demographic data; 7 questions inquired about physician's knowledge level about treatment of anaph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
(83 reference statements)
3
5
0
3
Order By: Relevance
“…In this context, it can be concluded that the older participants with longer work experience have not updated their knowledge of the epinephrine administration route in accordance with the current literature. Similar observations were made in recent studies in our country conducted by Tuncel et al [ 17 ] and in Tehran by Fakheri and Movahedi et al [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this context, it can be concluded that the older participants with longer work experience have not updated their knowledge of the epinephrine administration route in accordance with the current literature. Similar observations were made in recent studies in our country conducted by Tuncel et al [ 17 ] and in Tehran by Fakheri and Movahedi et al [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our study, including healthcare professionals from different healthcare institutions, showed that there was a lack of knowledge among healthcare professionals regarding the acute treatment of anaphylaxis such as the dose of epinephrine, and long-term therapy such as EAI doses, and prescribing rates. This lack of knowledge was similar to previous studies conducted in Turkey and different countries [ 16 17 18 19 20 ].…”
Section: Discussionsupporting
confidence: 91%
“…10 Recently in a 2020 study, a total of 120 physicians participated, the rate of correct answer about promptly choosing epinephrine as first drug of choice in treatment was 87.5%. 1 Similarly, in our study 88.7% of the participating physicians gave the correct answer about giving adrenalin as 1st choice in anaphylaxis as soon as possible. But about the route of administration, the ratio dropped to 66.7%.…”
Section: Discussionsupporting
confidence: 63%
“…Anaphylaxis is a life-threatening systemic reaction affecting all age groups. 1 High rates of hospitalization for anaphylaxis have been reported in different countries of the world. 2 The cases of anaphylaxis might have to be managed by doctors from different specialities.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] Nevertheless, the rate of pediatricians in our country choosing the epinephrine dose correctly has not changed significantly in the last seven years, in fact it has even decreased. 13,25 However, it is absolutely necessary to apply all steps in the management of a case of anaphylaxis immediately and correctly for preventing irrecoverable outcomes for the patient. 1,2 In this regard, in another study in which we assessed pediatricians' competence in anaphylaxis management through case scenarios, we ascertained that only 11.3% of the physicians were able to correctly apply all management steps from diagnosis to discharge recommendations.…”
Section: Discussionmentioning
confidence: 99%